The Effect of Family Support and Flash Card Education on Medication Adherence Among Elderly Patients with Type 2 Diabetes Mellitus - Fitriani, Anita; Budi, Setia; Agustina, Ani (Pustaka Media Publishing, 2026)
Suboptimal medication adherence remains a major challenge in managing type 2 diabetes mellitus among older adults, particularly in primary healthcare settings with limited long-term monitoring. Limited understanding of medication use and low family involvement are frequently associated with poor adherence behavior. This study aimed to assess changes in medication adherence following the implementation of family support and flash card–based education among elderly patients with type 2 diabetes mellitus. A pre-experimental one-group pretest–posttest design was conducted involving 88 purposively selected participants. Medication adherence was measured using a validated instrument. Data were analyzed using the Wilcoxon signed-rank test to compare pre- and post-intervention scores, Spearman correlation to examine the association between family support and adherence, and multiple linear regression to identify contributing factors. The results showed a significant increase in adherence scores after the intervention (p<0.001). Family support was moderately associated with medication adherence (r=0.462). Furthermore, the combined variables explained 33.0% of the variance in adherence (R²=0.330). These findings suggest that family-oriented visual education may serve as a feasible pharmaceutical care approach to support medication adherence among elderly patients, although further controlled studies are needed to confirm causal relationships.